Variations in the oxygen isotopic composition of precipitation in the Tianshan Mountains region and their significance for the Westerly circulation - Liu, Xiaokang; Rao, Zhiguo; Zhang, Xiaojian; Huang, Wei; Chen, Jianhui; Chen, Fahu (Journal of geographical sciences, 2015)
Proxy records of the oxygen isotopic composition of meteorological precipitation （δ^18Op） preserved in archives such as ice cores, lacustrine carbonates and stalagmite calcite are important for paleoclimatic studies. Therefore, knowledge of the variations and controlling mechanisms of modern δ^18Op on different time scales is necessary. Here, we investigate the linear correlations between δ^18Op and corresponding temperature and precipitation on monthly and inter-annual timescales, using data from the Urumqi （1986-2003） and Hotan stations of the Global Network of Isotopes in Precipitation （GNIP）, and δ^18O data from 4 ice cores in the adjacent Tianshan Mountains. Consistent with previous reported results, modern δ^18Op variations on a seasonal time scale in the Tianshan region are mainly controlled by a ＇temperature effect＇ （indicated by a significant positive correlation between δ^18Op and temperature）, with more positive δ^18Op values occurring in summer. However, on an inter-annual timescale, there is a weak inverse correlation between weighted average annual δ^18Op and annual average temperature at Urumqi station. This finding is supported by the inversely varying trends of δ^18Op data from 4 ice cores in the central and eastern Tianshan Mountains compared to annual average temperatures in the same region during the past 40-50 years. The data from Urumqi station and the 4 ice cores demonstrate that there is inverse correlation between δ^18Op and temperature on inter-annual to decadal time scales. Analysis of water vapor sources and pathways for the warm year of 1997 and the cold year of 1988 reveal that relatively more water vapor for the Tianshan region was derived from long-distance transport from high-latitude sources than during the warm year of 1997; and that more water vapor was transported from more proximal sources from mid- to low-latitude areas during the cold year of 1988. In addition, the δ^18Op values are more negative in the high latitude areas than those in mid- to low-latitude areas in the Eurasian continent at the upper wind direction of Tianshan Mountains region, according to the weighted averaged warm season （May to September）δ^18Op values for 14 GNIP stations in the years 1997 and 1988. Due to the distribution of δ^18Op within the Eurasian continent, the relative shift of water vapor sources between warm and cold years convincingly explains the observed variations of δ^18Op in the Tianshan Mountains region. Therefore, we conclude that variations in 518OD in this region are mainly controlled by changes in water vapor sources which are ultimately caused by northward and southward shifts in the Westerly circulation.